Osiąganie kompromisu potrzeb człowieka i przyrody - Karol Lewandowski (Studia Ecologiae et Bioethicae)
The article has exhibited that ecoengineering, consisting of the scheduled transformation of ecological systems is an alternate and equivalent method for handling natural environment in contrary to environmental technology, which consists of ecosystems protection against human activity. The human activity in the natural environment may consist of devastating, transforming, or protection trials. In a frame of protection (environmental technology) are attempts on limiting anthropopression, which means the influence of man on the natural environment by various restrictions - technological, legal, and ethical. Up to now transforming natural environment was considered as a necessary evil, connected with the technological impossibility to avoid anthropopression or political necessity to satisfy human needs.